The Foreign Policy of the European Union : Assessing Europe's Role in the World - Bindi, Federiga M. (Book collections on Project MUSE., 2010)
"Explores European foreign policy and the degree of European Union success in proposing itself as a valid international actor, drawing from expertise of scholars and practitioners in many disciplines from North America, Europe, Australia, and New Zealand. Addresses issues past and present, theoretical and practice-oriented, and country- and region-specific"--Provided by publisher.